حكم تولي أجهزة الذكاء الاصطناعي كتابة خطبة الجمعة وإلقائها - Majdi Tayseer Ibrahim Sulaiman (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
This research talks about an expected future calamity, which is that artificial intelligence devices will undertake the work of the Friday preacher, such as writing and delivering the sermon. The aim of the research is to show the jurisprudential ruling on this calamity, and it was followed in it according to the inductive purposeful analytical approach, and the result of the research was that the jurisprudential ruling on this issue There are many options between artificial intelligence devices writing the sermon themselves and receiving it, and this is not permissible from a legal standpoint. Because the robot is obligated to perform the Friday prayers, if he himself preaches, but if the imam stumbles in writing a disciplined Friday sermon, it is permissible for him to use these devices to write the sermon, on the condition that he reviews it after writing. Because there is no clear evidence that prevents it from being written solely by devices, this research contributes greatly to the jurisprudence of calamities because it laid the foundation for starting to look into t This is the future calamity